From the playing field to the classroom: The academic challenges for NCAA Division I athletes - Huml, Matt R.; Bergman, Mathew J.; Newell, Emily M.; Hancock, Meg G. (Journal for the study of sports and athletes in education, 2019)
Student-athlete graduation rates have significantly increased in recent years, with the NCAA believing their retention and graduation rates now outpace the general college student population. Even with these promising changes, student-athletes still face a litany of academic challenges during their higher education experience. The purpose of this study is to overview these academic challenges and provide potential remedies for universities and athletic department to assist student-athletes during their educational journey. The challenges reviewed in this study include: athletic identity, admissions, first-year experience, student-athlete relationship with the athletic department, academic clustering and time constraints, stereotypes of student-athletes, and student-athlete burnout. Recommendations include improving campus connections, both inside and outside the athletic department, establishing an academic advising model for athletic advisors, and implementing a summer bridge program for incoming student-athletes.